Responding to oil spill incidents in the marine environment using natural oil absorbents - جمل, ميساء; حازم كراوي; عبير سلطان (Latakia University Journal -Basic Sciences Series, 2022)
In this study, the optimal absorption time, maximum absorption, equilibrium curve and reusability were determined for four absorbent materials ( Typha domingensis , Datura stramonium, sorghum vulgare, Ammi visnaga) in the presence of four types of oil with different viscosities. The ability of the absorbent material to remove the spilled oil was related to several factors, the most important of which are the characteristics of the surface of the absorbent material, the viscosity of the oil and the thickness of its layer. The results showed that extending the sorption time had no effect on the sorption capacity of the sorbent materials for both diesel Lv and Mv While the absorption capacity was increased by extending the absorption time to 30 minutes for Hv . Trichomes of Typha showed a large absorption capacity, followed by Datura based on the results obtained, these natural materials can be used to remove oil because they have a high buoyancy, biodegradation, low cost and relatively high absorption capacity